FOSTERING STUDENTS’ READING COMPREHENSION SKILL TROUGH RCRR STRATEGY AT UNIVERSITY OF MUHAMMADIYAH OF BENGKULU - Putri Ramadhani; Yupika Maryansyah; Fetriani; Ivan Achmad N (LPPM STKIP AL MAKSUM, 2020)
Reading comprehension skill seems to be a complecated subject for students time to time. Teachers as the one who must train studentsto master the skill, keep struggling to utter the problem. This condition need teachers to find out probable solutions. One possiblesolution is by using specific strategy in taching, like the one called Read, Cover, Remember, Retell (RCRR). The purpose of thisresearch is to determine the effect of using Read, Cover, RCRR Strategy on students’ reading comprehension skill. The study isdesigned in quasi experimental method. The subjects of this research were students of English study program ofMuhammadiyah University of Bengkulu. In collecting data, researchers used a test. Result of the study shows that there was anincreasing scores on students’ reading comprehension skill who were taught by using RCRR. Based on the study done byresearchers, RCRR has brought positive effect on students reading comprehension skill. Therefore, the strategy is recommended to be used to teach reading comprehension in classes.